Directional Solidification with Constant Ice Front Velocity in the Ice‐Templating Process1 . Issue 1 (10th September 2015) - Stolze, Christian; Janoschka, Tobias; Schubert, Ulrich S.; Müller, Frank A.; Flauder, Stefan
Abstract : An exponential cooling function for the directional solidification of liquids with constant ice front velocities is investigated with respect to an enhanced control over the ice‐templating process. It is mathematically derived and set into relation to other cooling functions found in literature. A theoretical limit of applicability is discussed and a mathematical expression for the maximum sample size realizable with this new approach is derived. Experimental results from the time‐resolved direct measurement of the ice front evolution during the directional solidification of pure water and a ceramic β‐tricalcium phosphate (β‐TCP) suspension in a cooling room environment are presented. These results are compared to the results of numerical simulations. Ice front velocities from 10 to 50 µm s –1 are realized. Abstract : An exponential cooling function is investigated both theoretically and experimentally for the directional solidification of liquids with constant ice front velocities with respect to an enhanced control over the ice‐templating process. The function is mathematically derived, set into relation to other cooling functions found in the literature, and its theoretical limit of applicability is discussed.